Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae) - Framenau, Volker W.; Baehr, Barbara C. (Zootaxa, 2016)
The Australian wolf spider (Lycosidae Sundevall, 1833) genus Tasmanicosa Roewer, 1959 with Lycosa tasmanica Hogg, 1905 as type species is revised to include 14 species: T. godeffroyi (L. Koch, 1865), comb. nov. (= Lycosa tasmanica Hogg, 1905, syn. nov.; = Lycosa zualella Strand, 1907, syn. nov.; = Lycosa woodwardi Simon, 1909, syn. nov.); T. fulgor sp. nov.; T. gilberta (Hogg, 1905) comb. nov.; T. harmsi sp. nov.; T. hughjackmani sp. nov.; T. kochorum sp. nov.; T. leuckartii (Thorell, 1870), comb. nov. (= Lycosa molyneuxi Hogg, 1905, syn. nov.); T. musgravei (McKay, 1974) comb. nov.; T. phyllis (Hogg, 1905) comb. nov. (= Lycosa stirlingae Hogg, 1905, syn. nov.); T. ramosa (L. Koch, 1877), comb. nov.; T. salmo sp. nov.; T. semicincta (L. Koch, 1877) comb. nov.; T. stella sp. nov.; and T. subrufa (Karsch, 1878) comb. nov. Within the Australian wolf spider fauna, the genus Tasmanicosa can be diagnosed by the distinct pattern of radiating light and dark lines forming a “Union-Jack” pattern on the carapace. Male pedipalp morphology identifies the genus as part of the subfamily Lycosinae Sundevall, 1833 due to the presence of a transverse tegular apophysis with dorsal groove guiding the embolus during copulation. However, genital morphology is variable and a synapomorphy based on male pedipalp or female epigyne morphology could not be identified. Members of Tasmanicosa are comparatively large spiders (body length ca. 12–30 mm), that build a shallow burrow, which is sometimes covered with a flimsy trapdoor. Species of Tasmanicosa are largely a Bassian faunal element with preference for open woodlands and/or floodplains, although some species can be found into the semi-arid Australian interior. Two Australian wolf spider species may represent Tasmanicosa based on their original descriptions, but due to immature types in combination with the somatic similarities of all Tasmanicosa species, cannot be identified with certainty. They are therefore considered nomina dubia: Lycosa excusor L. Koch, 1867 and Lycosa infensa L. Koch, 1877. The type species of Orthocosa Roewer, 1960 is transferred to Tasmanicosa; however, in order to prevent some non-Australian wolf spiders in the genus Orthocosa to be transferred into Tasmanicosa, which is considered endemic to Australia, we here place these species into more appropriate genera based on their original descriptions pending a future revision of these species: Arctosa ambigua Denis, 1947 comb. reval.; Alopecosa orophila (Thorell, 1887) comb. nov.; Hygrolycosa tokinagai Saito, 1936 comb. reval. Orthocosa sternomaculata (Mello-Leitão, 1943) is considered a junior synonym of Hogna birabeni (Mello-Leitão, 1943) comb. nov.